(untitled) (Fiep Bulletin - online, 2014)
The aim of the study is to examine the differences in high school adolescents in motivational climate and enjoyment according to gender and if motivational climate infl uences enjoyment in physical activity.207 high school adolescents (males: n=118, age: 16±0.7 yrs, h:172.3±5.4 cm, weight: 67.4±11.9 kg; females: n=89, age: 15.9±0.8 yrs, h: 159.5±5.9 cm, weight:59.2±10.2 kg) were asked to complete enjoyment and motivational climate self-reported questionnaires during physical education lessons. Anova one-way was performed to examine the effect of gender on motivational climate and on enjoyment. A multiple regression analisys was also performed to examine if there were any gender differences in the prediction of enjoyment in physical activity.Data were analyzed by sPss ver.13 and signifi cance was set at p<0.05.signifi cant differences were found in favor of boys in ego-involving climate (p<0.001) and in positive enjoyment (p<0.05), while signifi cant differences were found in favor of females in task-involving climate (p<0.05). the regression analysis showed that taskinvolving climate (?=0.24, p<0.001) predicted a positive and signifi cant positive enjoyment in physical activity only in boys, not in females. According to several research, the result of this study showed that males were more perceived an ego-involving climate and positive enjoyment than females, while females were more likely to perceive a task-involving climate than boys. furthermore, task-involving climate predict positive enjoyment in physical activity only in boys. it’s necessary to adopt task involving teaching methods to promote adolescent’s physical activity enjoyment through secondary school years.